Functioning of it world market within transformational changes of global economic environment - Goncharenko, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
This article deals with informatization process of the countries and the peculiarities of the functioning of it world market within transformational changes of global economic environment. The paper studies the geographic structure of the IT market in the world economic system, the author ranks the countries according to the level of information and communication technologies development, determines the latest trends in the development of the global IT market and identifies the largest segments. According to the results of the research, strategic directions of IT industry development are defined, strategic goals of the information society development in Ukraine are generalized, Ukraine's position according to the Global Competitiveness Index, which determines the state of its informatization, is identified. The interconnection of the competitiveness of national economies with the development of the IT sector is proved. The conditions of the scenarios of IT development in Ukraine are systematized and their impact on increasing the revenues to the state budget is determined, recommendations for the development of the IT industry in Ukraine in the context of its integration into the information technologies world market are proposed